Hubungan Pengetahuan Tentang Teknik Menyusui yang Benar dengan Kejadian Puting Susu Lecet pada Ibu Nifas di BPM Bd. R di Desa Cibanteng Kabupaten Bogor Tahun 2023 - Zakiah, Lela; Apriliani, Berliana; Ramadhan, Bulan Suci; Nurhalisah, Sindy (Jurnal Kesehatan, 2024)
Sore nipples are one of the problems in breastfeeding, in which the nipples are injured due to inappropriate breastfeeding techniques or trauma to the nipples, resulting in cracks and the formation of fissures. Sore nipples will hinder the mother from breastfeeding because of pain and soreness. One thing that can prevent sore nipples is knowing and doing appropriate breastfeeding techniques. This study aims to determine the relationship between knowledge about correct breastfeeding techniques and the incidence of sore nipples in postpartum mothers in BPM Bd. R in Cibanteng Village, Bogor Regency in 2023. This research method is an analytical survey using a cross-sectional approach. The research instrument is a questionnaire given to 30 respondents. It was taken using a total sampling technique with sample criteria: mothers who breastfeed their babies. The statistical test used is Chi-square. From the results of this study, it was obtained that from the respondents in the category of good knowledge, the incidence of nipple abrasions was as many as five mothers (35.7%), while from the respondents in the category of poor knowledge was 15 mothers (93.8%) experience sore nipples. The results of the chi-square statistical test showed that the ρ value was 0.001<0.05. There is a relationship between knowledge and the incidence of sore nipples. The odds ratio result showed that mothers who are well-informed about the correct breastfeeding technique have a smaller risk of experiencing 0.037 times the incidence of blistering milk compared to those who are less knowledgeable. There are still many breastfeeding mothers who do not know the correct breastfeeding technique, which results in sore nipples.